Highly porous cellulose beads of controllable sizes derived from regenerated cellulose of printed paper wastes - Voon, L.K.; Pang, S.C.; Chin, S.F. (Elsevier, 2015)
Highly porous cellulose beads of controllable sizes were successfully prepared from regenerated cellulose of printed paper wastes based on a facile dissolution and controlled precipitation approach. Pure and dispersed cellulose fibers were isolated from finely ground paper wastes by undergoing initial pretreatment and maceration processes in sodium hydroxide solution (NaOH, 12 wt%). Dispersed cellulose fibers were subsequently dissolved in an ionic liquid (1-allyl-3-methylimidozoium chloride, AMIMCl) to form a homogenous cellulose solution. Highly porous cellulose beads of controllable sizes within the range of 0.4-2.2 mm in diameter were prepared by precipitation in a coagulation bath of ultrapure water under controlled conditions. Cellulose beads of various mean sizes exhibited substantially different specific surface area which ranged between 107 m2/g and 498 m2/g. Cellulose beads of biocompatibility, high porosity and specific surface area are therefore potentially useful as drug delivery carriers.